Calculation of Some Low-Lying Electronic Excitations of Barium Monofluoride Using the Equation of Motion (EOM)-CC3 Method with an Effective Core Potential Approach - Marko Horbatsch (Molecules)
Barium monofluoride (BaF) is a polar molecule of interest in measurements of the electron electric dipole moment. For this purpose, efforts are underway to investigate this molecule embedded within cryogenic matrices, e.g., in solid Ne. For a theoretical understanding of the electronic structure of such an embedded molecule, the need arises for efficient methods which are accurate but also able to handle a number of atoms which surround the molecule. The calculation for gas-phase BaF can be reduced to involve only outer electrons by representing the inner core of Ba with a pseudopotential, while carrying out a non-relativistic calculation with an appropriate basis set. Thus, the method is effectively at a scalar-relativistic level. In this work, we demonstrate to which extent this can be achieved using coupled-cluster methods to deal with electron correlation. As a test case, the SrF(<semantics>X<mspace width="0.166667em"></mspace>2Σ+→B<mspace width="0.166667em"></mspace>2Σ+</semantics>) transition is investigated, and excellent accuracy is obtained with the EOM-CC3 method. For the BaF(<semantics>X<mspace width="0.166667em"></mspace>2Σ+→A′<mspace width="0.166667em"></mspace>2Δ</semantics>, <semantics>X<mspace width="0.166667em"></mspace>2Σ+→A<mspace width="0.166667em"></mspace>2Π</semantics>, <semantics>X<mspace width="0.166667em"></mspace>2Σ+→B<mspace width="0.166667em"></mspace>2Σ+</semantics>) transitions, various coupled-cluster approaches are compared with very good agreement for EOM-CC3 with experimentally derived spectroscopic parameters, at the level of tens of <semantics>cm−1</semantics>. An exception is the excitation to the <semantics>A′<mspace width="0.166667em"></mspace>2Δ</semantics> state, for which the energy is overestimated by <semantics>230<mspace width="0.166667em"></mspace>cm−1</semantics>. The poor convergence behavior for this particular state is demonstrated by providing results from calculations with basis sets of n = 3, 4, 5)-zeta quality. The calculated excitation energy for the <semantics>B<mspace width="0.166667em"></mspace>2Σ+</semantics> state agrees better with a deperturbation analysis than with the effective spectroscopic value, with a difference of <semantics>120<mspace width="0.166667em"></mspace>cm−1</semantics>.